(untitled) (Research, Society and Development, 2020)
Objective: to reflect on patient safety standing out their recognition for ethics in nursing care. Method: This is a reflective study about content essential for patient safety; Highlighted for: Axel Honneth’s safety culture and recognition. Results: By recognizing their values and capacity, subjects tend to raise their self-esteem and motivate themselves to exercise their autonomy. Self-esteem, awareness of the recognition of human beings in their dignity, and rights to decent treatment with less risk contribute to the development of professionals who are more interested in offering qualified and safe services. Conclusion: It was concluded that this perspective reflects, among nursing professionals, a concern with the recognition of users, and the duty not to cause harm to the patient in the practice of professional practice.